14+6x=-2(-8x+3)

Simple and best practice solution for 14+6x=-2(-8x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14+6x=-2(-8x+3) equation:



14+6x=-2(-8x+3)
We move all terms to the left:
14+6x-(-2(-8x+3))=0
We calculate terms in parentheses: -(-2(-8x+3)), so:
-2(-8x+3)
We multiply parentheses
16x-6
Back to the equation:
-(16x-6)
We get rid of parentheses
6x-16x+6+14=0
We add all the numbers together, and all the variables
-10x+20=0
We move all terms containing x to the left, all other terms to the right
-10x=-20
x=-20/-10
x=+2

See similar equations:

| 12x^2-168x+147=0 | | 14n+22=8(2n-10) | | 7f+18=10f-9 | | 2(3a+4)=2(2a+5) | | 7(m+3)=5m-9 | | -(3n+4)=-2(n-7) | | -4(2x-1)=2(x+6) | | 5(a-8)=3a+6 | | 5(x+6)=7x-12 | | 7x+2=3x−9 | | 2*(x+3)=12-x | | X-3×3=x-5×5 | | X-3/5=x-5/3 | | 6x+40=2x+50 | | 15x/10-36/10=2x-3 | | 2a+3(a-6)=14 | | 5+20x=7+12x | | 2n+4n=-2 | | x-2/3=2/9x= | | 2x+5+5+4x=x+20 | | 0.06g=0.87g | | 2p+6(1+P)=5p-12 | | (y+2)(y+3)=0 | | 13-6x=-23 | | 1/2y^2+3/4y=5 | | 10/m-10/m+5=1 | | d/65-3=d/130 | | x2(x-9)(2x+1)=0 | | 15-43y-6y^2=0 | | 5(3-3v)=15-3v | | 184=0,56x | | 6a+5=5+6a |

Equations solver categories